Analysis of the Soil Data Using Classification Techniques for Agricultural Purpose - Hemageetha, N; Nasira, GM (International Journal of Computer Sciences and Engineering, 2025)
India has more than sixty percent of its total area for agricultural purpose. Agricultural sector is the backbone for all the developing countries. Agriculture sector continue to play a vital role in the development of the economy. Data Mining supports decision making process and prediction. Agriculture needs the decision support system in variety of ways such as type of crop to be cultivated. There were many researches going on to support the agriculture using data mining. Analyzing soil provides major contribution to the support of the farmers. This paper analyzing Salem District soil data using data mining techniques.